The reasons why patients abscond from public hospitals in southeastern Iran: a qualitative study - Mahnaz Moradpour; Mohammadreza Amiresmaili; Mahmood Nekoei-Moghadam; Tania Dehesh (BMC, 2021)
Abstract Background Patient absconding from hospital is one of the permanent issues the hospitals face, which poses many risks and challenges to the patient, hospital, and society. The present study aimed to identify the reasons for patient absconding behavior for public hospitals in southeastern Iran. Methods The present study is a qualitative study which was conducted at three public hospitals in southeastern Iran using purposive sampling through semi-structured interviews with 63 informants involved in patient treatment process. Data were analyzed using Colaizzi content analysis (CCA) method. Results Three main themes of economic, social factors, and factors related to the hospital covering 15 subthemes were identified to explain the reasons for patients absconding behavior. Conclusion There are many reasons for reducing patients absconding from hospitals, and one of the main reasons is the patients' economic and social problems. The absconding behavior can lead to harm and problems for patients, and some emotional and occupational consequences for the employees and nurses. Paying attention to this issue and considering some courses of action to prevent patient absconding might lead to a considerable promotion of public trust and eliminate many problems for hospitals.